Retained Intraocular Foreign Body - Iqbal, Mustafa (Pakistan Journal of Ophthalmology, 2010)
BACKGROUND Intraocular foreign bodies (IOFBs) account for almost 40% of penetrating ocular injuries1-3. 75% of the IOFBs lodge in the posterior segment4. Retained intraocular foreign bodies most commonly result from occupational activities and predominantly involve males in 3rd to 4th decade5. Most sustain injury while hammering a metal with metal and 80% cases have metallic IOFBs6. The hammer-chisel injury is the most common cause of the IOFB in adults7. Other emerging causes like fire arm injuries and blast injuries are becoming common.